Analyzing Asset Investment: Taking Three Large Semiconductor Companies as Examples - Ren, Jiazhe (Transactions on Economics, Business and Management Research, 2024)
This article provides a comprehensive financial analysis of three major semiconductor companies: ASML, TSMC and AMD. These companies occupy a very high position in semiconductor manufacturing, design and innovation and form an ecosystem of advanced semiconductor technology products. The objective of this study is to assess the attractiveness of these companies to different types of investors in terms of investment strategies such as value investing, income investing, PEG investing, index investing, ratio analysis investing, momentum investing, insider buying investing, stocks buyback and smart money investing. Analysis of the latest financial data shows that index investors, stocks buyback investors and smart investors are more likely to invest in these three companies. According to the financial data ratio analysis, investors who favour ASML include investors who use momentum strategies and investors who use ratio analysis. The same is true for TSMC, where bullish investors include those using ratio analysis, momentum, valuation and income investing. The results of this study can be used to recommend individual investment strategies to investors to help them achieve optimal financial returns in the technology sector. In addition, the study can be used as a valuable source of information for first-time investors and provide them with guidance on how to navigate the sector.